RELMARK: An innovative algorithm for preprocessing of transactional business data - Mohd Shaharanee, Izwan Nizal; Mohd Jamil, Jastini; Hashim, Kamarul Faizal (American Scientific Publishers, 2015)
Association rule mining is a popular research topic due to many useful applications.The initial task in producing association rule is to ensure that only suitable data formats are fed into the mining process.Providing a correct data format for association rule mining is an essential and crucial task as wrong data will yield wrong results and interpretations.In this research work, an efficient algorithm for converting relational data format into transactional data format is presented.This transactional data format suited the SAS Enterprise Miner Software for association rule mining technique. The experiments using synthetic and real world data demonstrate the effectiveness of the algorithm.